Новые сведения о корольках Крыма - Костин, Ю.В. (Вестник зоологии, 1972)
On the basis of field observations, collection materials and literary data, the problem щ the character of Regulus regulus L. and R. ignicapillus Temm . staying in the Crimea is revised. Regardless of the opinion spread in literature, Regulus regulus does not nest in the Crimea and only regularly winters and is met with on their flight. At the same time the author collects in the Crimea a series of Regulus ignicapillus for the first time. Obtaining of birds in nesting period (April — June), good development of gonads and some other facts permits one to suppose Regulus ignicapillus nesting in pine woods of the Mountain Crimea.